Evaluation of Antihypertensive Treatment Inoutpatients at Batang Beruh Helath Centre Sidikalang - Indra Ginting; Asriwati Amirah; Mayang Sari (Journal La Medihealtico, 2021)
Hypertension is a cardiovascular disease with a high prevalence and risk of death in developed and developing countries with blood pressure reach ≥140/90 mmHg. Hypertension is the 3rd cause of death after stroke and tuberculosis, reached 6.7% of the population of deaths at all ages in Indonesia. Results of Basic Health Research (Riskesdas) Balitbangkes showed that the national prevalence of hypertension reached 31.7%. The National Formulary (Fornas) is a list of drugs compiled based on the latest scientific evidence by the National Committee for the Compilation of the Fornas. Evaluation of the appropriateness of antihypertensive treatments in outpatients at Batang Beruh Health Centre Sidikalang seen from the National Formulary was the aim of this study. This research is non-experimental, quantitative descriptive was conducted in May - July 2019 at Batang Beruh Health Centre Jl. Pahlawan Sidikalang, Sidikalang District of Dairi, North Sumatra. The population was 231 hypertensive patients using antihypertensive drugs, with sampling using the Slovin formula, amounted to 70 respondents. Based on the research conducted, in the Calcium Antagonist group, the names of the antihypertensive drugs used are Amlodipine and Nifedipine. Meanwhile, in the ACEIs group, the drug used is Captopril. Whereas in the Angiotensin II receptor antagonist group, the drugs used are Micardis, Valsartan and Candesartan. Whereas in the Diuretic group, the antibiotic used is Furosemide.